Assessing Constitutionality of Amendment by Appendix Model in Indonesia - Bimo Fajar Hantoro (Walisongo Law Review (Walrev), 2026)
This research aims to analyze the “amendment by appendix” model as employed in Law 1/2026 and to review its formal constitutionality. This doctrinal legal research combines statutory and conceptual approaches. The findings show that while the “amendment by appendix” model offers functional legislative efficiency, it operates as a distinct and novel drafting technique that remains unregulated within the strict guidelines of Appendix II of Law 12/2011 and its amendments. The precedent of Decision 91/PUU-XVIII/2020 is instructive, mandating that every novel legislative drafting technique must be regulated prior to its use. Consequently, the absence of the “amendment by appendix” model in the established guidelines renders its practice in Law 1/2026 prima facie unconstitutional on procedural grounds. While Law 1/2026 remains constitutional under the presumption of validity absent a formal judicial review, ex-post measures to cure its defects may prove futile. As a policy implication, lawmakers must proactively amend Law 12/2011 to explicitly legitimize the model, ensuring its valid future application while mitigating the risk of constitutional invalidation. Penelitian ini bertujuan untuk menganalisis model “perubahan melalui lampiran” sebagaimana dipraktikkan dalam UU 1/2026 dan meninjau konstitusionalitasnya secara formil. Penelitian hukum doktrinal ini menggabungkan pendekatan perundang-undangan dengan pendekatan konseptual. Temuan penelitian menunjukkan bahwa kendatipun model ini menawarkan efisiensi secara fungsional dalam proses legislasi, model tersebut merupakan teknik perancangan perundang-undangan baru yang belum secara tegas diatur dalam Lampiran II UU 12/2011 beserta perubahannya. Putusan 91/PUU-XVIII/2020 menjadi relevan dengan menegaskan bahwa setiap teknik penyusunan peraturan perundang-undangan harus diatur terlebih dahulu sebelum digunakan. Akibatnya, belum diaturnya model tersebut menjadikan penerapannya dalam UU 1/2026 inkonstitusional secara prima facie karena cacat prosedural. Kendatipun UU 1/2026 tetap dianggap konstitusional berdasarkan asas praduga keabsahan sebelum adanya putusan pengujian undang-undang yang menyatakan sebaliknya, upaya ex-post untuk memperbaiki cacat prosedur besar kemungkinan akan sia-sia. Sebagai implikasi kebijakan, pembentuk undang-undang harus secara proaktif mengubah UU 12/2011 untuk melegitimasi model tersebut, guna memastikan keabsahan penggunaannya di masa depan sekaligus memitigasi risiko inkonstitusionalitas. Keywords: amendment; appendix; formal constitutionality.